Diagnostic accuracy of transabdominal ultrasound in respect to transvaginal ultrasound in diagnosing ectopic pregnancy in a tertiary care hospital of Kolkata taking histopathology as gold standard: a prospective study - Das, Prasun; Saha, Raj; Bhattacharyya, Srijak; Basu, Swadha Priya; Das, Debopriya (International Journal of Research in Medical Sciences, 2021)
Background: Ectopic pregnancy (EP) represents an important cause of acute pelvic pain in women of reproductive age. Initial evaluation consists of appropriate history and clinical examination followed by pelvic ultrasonography (US) and hormonal assays. Objective of the study was to measure diagnostic accuracy of TAS in respect to TVS in detecting ectopic pregnancy. Methods: This prospective cross sectional study was done for 1 year duration in Nilratan Sircar Medical College and Hospital, Kolkata. 50 patients with suspected ectopic pregnancy were transferred from Gynae emergency ward and trans-abdominal, transvaginal ultrasound were subsequently performed on each. The results were corroborated with histopathology reports.. Results: Diagnostic parameters of TAS in respect to HPE:sensitivity 75.5, specificity-80,PPV-97.1, NPV-26.6 (all in percentages). Diagnostic parameters of TVS in respect to HPE:sensitivity 86.6, specificity-80, PPV-97.5, NPV-40 (all in percentages). Conclusions: Sonography by transvaginal route stood way ahead of trans abdominal scan in terms of all diagnostic parameters to correctly evaluate ectopic pregnancy.